Rapidly progressive medulloblastoma initially mimicking idiopathic intracranial hypertension and Chiari I malformation: A case report. (August 2021) - Noiphithak, Raywat; Mektripop, Nattakitta; Thamwongskul, Chatchai
Abstract: Introduction: Medulloblastoma (MDB) often causes signs and symptoms of elevated intracranial pressure (ICP) with imaging findings of mass lesion. Here, we report a case of MDB who initially presented with clinical features imitating idiopathic intracranial hypertension (IIH) and Chiari I malformation (CIM). Case presentation: A 19-year-old man had clinical symptoms of elevated ICP without mass lesion on imaging. He was initially diagnosed with IIH and CIM, which underwent shunt surgery and posterior fossa decompression. Later on, he had recurrent symptoms, and the new imaging revealed the development of MDB in the right cerebellar hemisphere. After tumor resection, the patient rapidly deteriorated with spinal metastases. Discussion and conclusion: Management of the coexistence between IIH and CIM in patients with rising ICP is complicated. MDB is one of the aggressive malignant brain tumors showing a wide range of imaging features, including non-enhancing mass. Therefore, recognizing the possibility of brain tumors mimicking IIH or CIM is crucial. Highlights: The coexistence of idiopathic intracranial hypertension (IIH) and Chiari I malformation (CIM) is complicated. Medulloblastoma (MDB) can present with a wide range of imaging features, including non-enhancing mass. Exclusion of the secondary cause of rising intracranial pressure is necessary before making the diagnosis of IIH or CIM Early diagnosis, including subtype of MDB, and urgent treatment are crucial for better outcome.